Meningkatkan kemampuan motorik halus anak melalui kegiatan menggunting bahan alam di TK Masyithoh 04 Pekalongan - Nur Hidayah (Action Research Journal, 2021)
Cutting is essentially an activity to develop fine motor skills in the individual, fine motor changes develop due to the individual's efforts, including regular exercises and activities according to the child's abilities and development. In Masyithoh 04 Pekalongan Kindergarten in the development of fine motor skills, most children cannot complete tasks on time, in learning to cut using paper media so that the learning process looks monotonous and children feel bored quickly, the learning media used is less varied for that we need media The interesting thing is cutting with natural material media to improve children's fine motor skills. The purpose of this study was to obtain an overview of the objective conditions of the implementation of improving fine motor skills through cutting activities with natural material media in Masyithoh Kindergarten 04 Pekalongan City. This type of research uses classroom action research. By using pre cycle, cycle I and cycle II, the results of the study showed that there was an increase in children's fine motor skills through cutting activities with natural materials from Pre cycle 13.3%, Cycle I 26.6% and Cycle II 60%, after In the second cycle of learning improvements, it appears that there is a significant increase in the results of children being able to do cutting activities with natural materials.